Kapasitas liminal: Kompetensi kepemimpinan Kristen dalam menavigasi ambiguitas dan transisi eklesiologis - Yudhy Sanjaya (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
Contemporary churches exist in a transitional phase marked by paradigmatic shifts, digital disruption, and institutional trust crises. This condition demands a reconstruction of Christian leadership models capable of functioning in transformative ways amid ambiguity. This article constructs the concept of